Correction to: Potential cost-savings from the use of the biosimilars filgrastim, infliximab and insulin glargine in Canada: a retrospective analysis - Kerry Mansell; Hishaam Bhimji; Dean Eurich; Holly Mansell (BMC, 2019)
In the original publication of this article [1], there is a mistake in the Fig. 2a, 2b, and 2c.